2015
DOI: 10.1371/journal.pone.0119964
|View full text |Cite
|
Sign up to set email alerts
|

Complete Protection of Mice against Lethal Murine Cytomegalovirus Challenge by Immunization with DNA Vaccines Encoding Envelope Glycoprotein Complex III Antigens gH, gL and gO

Abstract: Human cytomegalovirus infects the majority of humanity which may lead to severe morbidity and mortality in newborns and immunocompromised adults. Humoral and cellular immunity are critical for controlling CMV infection. HCMV envelope glycoprotein complexes (gC I, II, III) represent major antigenic targets of antiviral immune responses. The gCIII complex is comprised of three glycoproteins, gH, gL, and gO. In the present study, DNA vaccines expressing the murine cytomegalovirus homologs of the gH, gL, and gO pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…An essential role of the gH/gL/gO complex for pathogenesis of murine CMV (MCMV) was recently demonstrated in a mouse model: a gO-deficient MCMV mutant was unable to establish infection in mice (32), indicating that gO plays a pivotal role for host-to-host transmission of CMV. Immunization of mice with gH/gL/gO leads to full protection from otherwise lethal MCMV infection (33). For HCMV it was recently demonstrated that gH/gL/gO interacts with the cellular receptor platelet-derived growth factor receptor alpha (PDGFR-␣) (34).…”
mentioning
confidence: 99%
“…An essential role of the gH/gL/gO complex for pathogenesis of murine CMV (MCMV) was recently demonstrated in a mouse model: a gO-deficient MCMV mutant was unable to establish infection in mice (32), indicating that gO plays a pivotal role for host-to-host transmission of CMV. Immunization of mice with gH/gL/gO leads to full protection from otherwise lethal MCMV infection (33). For HCMV it was recently demonstrated that gH/gL/gO interacts with the cellular receptor platelet-derived growth factor receptor alpha (PDGFR-␣) (34).…”
mentioning
confidence: 99%
“…Research in this area has focused on either attenuation of the live virus or the use of [8]. CMV is a large virus with a 230 kb double-stranded DNA genome coding for approximately 200 proteins of which UL55 (also known as glycoprotein B) has been recognized as a key immunogen eliciting strong immune responses in humans and a target for vaccine development [8,9]. Antibody production is considered a major defense against viruses and HCMV antiglycoprotein B (anti gB) is detected in all infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody production is considered a major defense against viruses and HCMV antiglycoprotein B (anti gB) is detected in all infected individuals. gB is a highly conserved, 906 amino-acid long protein consisting of an ectodomain, a hydrophobic region, a transmembrane and a cytoplasmic domain which is required for viral entry into all cell types including placental precursor cells and cell to cell spread of the virus [8][9][10]. Several antibodybinding sites have been identified on gB of which two domains containing three antigenic sites are capable of eliciting neutralizing antibodies during natural infection [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations